2015
DOI: 10.1080/10106049.2015.1062053
|View full text |Cite
|
Sign up to set email alerts
|

Earth observation-based multi-scale impact assessment of internally displaced person (IDP) camps on wood resources in Zalingei, Darfur

Abstract: This study describes the development of a semi-automatic object-based image analysis approach for the detection and quantification of deforestation in Zalingei, Darfur, in consequence of the increasing concentration of refugees or internally displaced persons (IDPs) in the region. The classification workflow is based on a multi-scale approach, ranging from the analysis of high resolution SPOT-4 to very high resolution IKONOS and QuickBird satellite imagery between 2003 and 2008. The overall accuracy rates for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Clearly, these pressures impact wild plant resources, particularly in terms of their use as "famine food" and as animal fodder, firewood, and construction wood (e.g. see Spröhnlea et al 2016). In addition, nomadic pastoralists and the Fur farmers in West Darfur, today represented by distinct political groups, may place different priorities on each of the species we surveyed; our study focused on assessments by indigenous Fur farmers, who make up over 75% of the rural population, and who use both established farmland, and upland pastures for seasonal pastoralism.…”
Section: Species and [Family]mentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, these pressures impact wild plant resources, particularly in terms of their use as "famine food" and as animal fodder, firewood, and construction wood (e.g. see Spröhnlea et al 2016). In addition, nomadic pastoralists and the Fur farmers in West Darfur, today represented by distinct political groups, may place different priorities on each of the species we surveyed; our study focused on assessments by indigenous Fur farmers, who make up over 75% of the rural population, and who use both established farmland, and upland pastures for seasonal pastoralism.…”
Section: Species and [Family]mentioning
confidence: 99%
“…There is growing evidence of localized depletion of species with high TIV values, particularly around IDP camps (Spröhnlea et al 2016). The urgency of this situation suggests that scientists and local communities should collaborate to track the use, and abundance of each of these multi-use species.…”
Section: Species and [Family]mentioning
confidence: 99%
“…The monitoring of refugee camp expansion and the resultant degradation of the environment and forest cover change using earth observation data such as aerial photography, LiDAR, and high-resolution satellite imagery (i.e., Quick bird, IKONOS) has been seen quite often in practice [29][30][31][32]. Different methodologies with varying degrees of resources, costs, accuracy, expertise and technology have been applied in tracking refugee camps and assessing environmental impacts on the camps' surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lodhi et al (1998) [33] monitored land cover changes and environmental impacts using Landsat imagery with unsupervised classification in the Siran Valley in northern Pakistan resulting from an influx of Afghan refugees in the early 1990s. Spröhnle et al (2016) [32] observed the impacts of internally displaced person (IDP) camps on wood resources in Zalingei, Darfur using high resolution satellite imagery between 2003 and 2008. Their research found that increasing IDP camps caused a considerable decrease in woody vegetation surrounding the camp area.…”
Section: Introductionmentioning
confidence: 99%
“…Previous vegetation cover change research in Darfur [ 29 , 31 , 32 ] was done before 2016. All those studies were conducted in Central, Western, and North Darfur.…”
Section: Introductionmentioning
confidence: 99%